Tinjauan Perspektif Mahasiswa Universitas Jambi Terhadap Efektivitas Program Affiliate Marketing Di Platform Shopee Dan Tiktok Shop - Ary Dean Amry; Jannatul Aulia; Dinda Imadatul Biladiyah; Melyna Susila Rosalinda; Muhammad Wahyu Zahran; Sanny Triwanda Huta Julu (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study aims to analyze how much influence the effectiveness and factors of affiliate marketing in increasing the level of satisfaction of Jambi University students. This research method uses quantitative research methods. The object of this study was Jambi University students totaling 100 respondents. Based on the results of the T test and F test variables (X1), the effectiveness of affiliate marketing (X2), affiliate marketing factors obtained significant values of 0.000 < 0.005. So it can be concluded that the variables (X1) of affiliate marketing effectiveness (X2) of affiliate marketing factors together influence in increasing the level of satisfaction of Jambi University students. Based on the results of the adjusted R 2 test in this study, an adjusted R 2 value of 0.472 was obtained. This shows that the level of satisfaction of Jambi University students is influenced by the effectiveness and factors of affiliate marketing and is 47.2%, while the remaining 52.8% is influenced by other factors that were not studied in this study.